2019
DOI: 10.1039/c9sc02032b
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial silver targets glyceraldehyde-3-phosphate dehydrogenase in glycolysis of E. coli

Abstract: We report for the first time that antimicrobial Ag+ targets the glycolytic pathway through inhibiting the key enzyme of GAPDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 55 publications
(66 reference statements)
6
33
0
Order By: Relevance
“…Surprisingly, the presence of NAD + eliminated the positive electron density near the Cys149. This change also stabilized the secondary structure of the alpha helix, which recovered its commonly observed conformation [33,34,38,39]. However, we could not build the NAD + moiety due to its low occupancy (0.7); this data might be in agreement with previous studies in which the affinity towards NAD + is decreased for the oxidized enzyme [48].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Surprisingly, the presence of NAD + eliminated the positive electron density near the Cys149. This change also stabilized the secondary structure of the alpha helix, which recovered its commonly observed conformation [33,34,38,39]. However, we could not build the NAD + moiety due to its low occupancy (0.7); this data might be in agreement with previous studies in which the affinity towards NAD + is decreased for the oxidized enzyme [48].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, soaking the crystals with NAD + highly reduces the presence of the large electron density around Cys149 and stabilizes the secondary structure of the alpha helix in only one conformation (Figure 4a,b). All residues recovered the conformation previously reported in other EcG3PDH models [33,34,38,39].…”
Section: Double Conformation Of the Helix (Residues 206-214)supporting
confidence: 79%
“…[40][41][42] Furthermore, new advances have revealed detailed information on possible modes of action for silver-based antimicrobial compounds. 43,44 Silver itself is known to be an antimicrobial agent, with varying activity depending on form (salts vs. nanoparticles vs. colloidal forms), so analysis of activity of silver complexes is complicated by this inherent activity. 45,46 Altogether, our data support the published literature and highlights that silver compounds are a proven starting point for preparation of new potential antibiotic compounds.…”
Section: 5%mentioning
confidence: 99%
“…A possible hypothesis to explain this variation could be the downregulation of the glycolytic conversion of glucose to pyruvate, which is consistent with the observed significant reduction in pyruvate excretion. An early work has shown that silver ions could inactivate yeast hexokinase due to binding with protein thiol groups, while a recent metallomics work has highlighted glycolytic enzymes as primary targets of ionic silver in E. coli . Additionally, similar findings, namely decreased activities of hexokinase and enolase, have been recently reported in mouse macrophages exposed to AgNPs .…”
Section: Discussionmentioning
confidence: 75%